Biosurfactant production by Antarctic-derived yeasts in sugarcane straw hemicellulosic hydrolysate - Chaves, Flaviana da Silva; Brumano, Larissa Pereira; Franco Marcelino, Paulo Ricardo; da Silva, Sílvio Silvério; Sette, Lara Durães [UNESP]; Felipe, Maria das Graças de Almeida (Springer Nature, 2021)
The Antarctic continent is a reservoir of new genetic resources to the bioprospection of microorganisms adapted to the polar conditions and capable to produce molecules with differentiated properties. Biosurfactants are a promising alternative to replace synthetic surfactants due to their eco-friendly characteristics and the possibility of being produced from raw materials, such as lignocellulosic biomass. The aim of the current study was to evaluate the biosurfactants produced by Antarctic yeast strains using detoxified sugarcane straw hemicellulosic hydrolysate (DSSHH). Therefore, the biosurfactant production, using xylose as the carbon source, was first evaluated in semi-defined medium and subsequently in DSSHH. The Naganishia adellienses L95 showed the highest emulsification index (52%) and total xylose consumption (40 g.L−1) in DSSHH. The biosurfactant produced by the yeast strain L95 was partially characterized, and its emulsion remained stable under low-temperature conditions (0 and 4 °C), at high salt concentration (10%), and alkaline condition. The screening of yeasts for the attainment of natural products that have potential biotechnological applications is of great importance. The results showed the potential of L95 to produce biosurfactants in DSSHH.
Keywords: Antarctica; Industrial biotechnology; Microbiology; Screening; Sugarcane straw